Meninjau dari Sightless : Indra Perasa Arsitektur - M Galieh Gunagama; Aesha Mutiara Nurulhuda; Nisaaul Muflihaturrahman (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2022)
The hierarchy of the five senses, from greatest sense of sight to lowest sense of touch, is used to understand them. This is the fundamental idea—that humans almost never disregard the role that their sense of sight plays in the course of their lives. It's crucial to comprehend architectural space from a different point of view in order to later accomplish a deeper emotional approach to the user, which is also a distinctive space experience from other designs without an architectural sense. approach. A character in this Sightless 2020 study is suddenly become blind after being struck by a fan strike and is compelled to comprehend the local spatial architecture using other non-visual senses